PROFIL PERESEPAN PENGOBATAN INFEKSI PADA IBU HAMIL DI KLINIK KEBIDANAN DAN KANDUNGAN RUMAH SAKIT CAHYA KAWALUYAN - Mercya, Yovita; Tarida Sinaga, Deborah; Anggoro Parulian, Adi (Jurnal Farmamedika (Pharmamedika Journal), 2025)
During pregnancy, women are more susceptible to infections due to hormonal changes and a weakened immune system. This study aims to determine the characteristics of maternal age, gestational age, gravida, diagnosis, and the profile of anti-infective prescriptions for pregnant women at the Obstetrics and Gynecology Specialist Clinic of Cahya Kawaluyan Hospital. This observational study utilized medical record data of pregnant women receiving outpatient anti-infective treatment during 2023. Using purposive sampling techniques, data were obtained from 44 patients who received anti-infective drugs according to inclusion criteria. The results showed that the majority of pregnant patients were aged 20-35 years (88.6%), with a gestational age of the third trimester (54.5%), and multigravida (56.8%). The most common diagnosis among pregnant women receiving anti-infective treatment was infectious diseases in pregnancy (code O98), accounting for 77.3%, with upper respiratory tract infections being the most frequent (50%). The most commonly used anti-infective drug was cefadroxil, reaching 47.73%, both as a single antibiotic and in combination with other antibiotics. Additionally, ceftriaxone 1 gram injection was often used for prophylaxis before delivery or other complicating conditions. According to the USA-FDA safety category for pregnant women, the most used category of drugs was Category B, accounting for 53.84%.